Implementasi manajemen risiko operasional terhadap kebocoran data nasabah pada bank syariah di Indonesia - Sunairah, Sunairah (Maliki Interdisciplinary Journal, 2024)
In the era of globalization and the ever-evolving economic dynamics, financial institutions, especially Sharia banks in Indonesia, are becoming increasingly vital. This article discusses the concept of risk management in Sharia financial institutions, particularly Sharia banks in Indonesia, and highlights the risks within the scope of Sharia banking in Indonesia. The method employed in this research involves utilizing literature analysis through a literature review technique. The risks faced by Sharia banks include credit or financing risk, market risk, liquidity risk, operational risk, legal or regulatory risk, reputation risk, strategic risk, compliance risk, yield risk, and investment risk. The risk management process, risk levels, types of risks, and risk management limits are also addressed in this article. Furthermore, the issue of data leakage in Sharia banks and the methods used to mitigate data leakage risks are also highlighted. Keywords : Risk management, Sharia bank, types of risk, data leakage, and limit.